Diagnostic and prognostic value of high-sensitivity cardiac troponin T in patients with syncope - Christ, Michael; Bertsch, Thomas (The American journal of medicine, 2015)
Objective: We examined the diagnostic and predictive value of high-sensitivity cardiac troponin T (cTnThs) in patients with syncope. Methods: We performed an analysis of consecutive patients with syncope presenting to the emergency department. The primary end point was the accuracy to diagnose a cardiac syncope. In addition, the study explored the prognostic relevance of cTnThs in patients with cardiac and noncardiac syncope. Results: A total of 360 patients were enrolled (median age, 70.5 years; male, 55.8%; 23.9% aged >80 years). Cardiac syncope was present in 22% of patients, reflex syncope was present in 40% of patients, syncope due to orthostatic hypotension was present in 20% of patients, and unexplained syncope was present in 17.5% of patients. A total of 148 patients (41%) had cTnThs levels above the 99% confidence interval (CI) (cutoff point). The diagnostic accuracy for cTnThs levels to determine the diagnosis of cardiac syncope was quantified by the area under the curve (0.77; CI, 0.72-0.83; P < .001). A comparable area under the curve (0.78; CI, 0.73-0.83; P < .001) was obtained for the predictive value of cTnThs levels within 30 days: Patients with increased cTnThs levels had a 52% likelihood for adverse events, patients with cTnThs levels below the cutoff point had a low risk (negative predictive value, 83.5%). Increased cTnThs levels indicate adverse prognosis in patients with noncardiac causes of syncope, but not in patients with cardiac syncope being a risk factor for adverse outcome by itself. Conclusions: Patients with syncope presenting to the emergency department have a high proportion of life-threatening conditions. cTnThs levels show a limited diagnostic and predictive accuracy for the identification of patients with syncope at high risk.